Study on mergers and acquisitions and their corresponding market reaction during the subprime mortgage financial crisis. - Tan, Joyce Siyi. (2011)
Mergers & Acquisitions (M&A) have seen growing importance as many firms utilize this strategy as a means to increase synergy, gain market control or to diversify into other areas. This paper aims to analyse whether a sudden and drastic change in the economic surrounding will impact the acquirers’ returns and observe how the market responds to the event of an announcement of an M&A deal. In particular, we explore two time periods with different economic surroundings and compare our findings with respect to how it is influenced by factors such as target status, method of payment and leverage of the acquirer. The results may provide some insights to firms who intend to engage in M&A during uncertain times. Our analysis suggests that acquiring private targets or using cash as a payment method will reap positive market reaction during normal economic conditions where the market is stable. However, it recommends that using leverage during the financial crisis will result in a negative market reaction as the market is uncertain and investors are more risk-averse. Lastly, it is more likely that the market will respond more negatively during times of distress than normal economic conditions.